2004
DOI: 10.1111/j.1439-0485.2004.00020.x
|View full text |Cite
|
Sign up to set email alerts
|

The Skeleton Eroding Band Disease on Coral Reefs of Aqaba, Red Sea

Abstract: The occurrence and distribution of the coral disease Skeleton Eroding Band (SEB) has been studied at the Jordanian coast in the Gulf of Aqaba, the northernmost extension of the Red Sea. The SEB syndrome is caused by the colonial, heterotrich ciliate Halofolliculina corallasia: an advancing front of these protists destroys polyps, coenosarc, and surface of the coenosteum. In recent years SEB was registered in reefs of Australia, Mauritius, and the Red Sea. Along the Jordanian coast, disease frequency at four s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 29 publications
1
30
0
1
Order By: Relevance
“…In the Indo-Pacific, SEB is more prevalent than any other coral disease (Page and Willis 2008) and is more common in polluted and warmer waters (Antonius and Lipscomb 2001;Willis etal. 2004;Winkler et al 2004). In contrast, the prevalence of the Caribbean ciliates appears to be higher in oceanic versus coastal human-influenced reefs (Croquer et al 2006a).…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…In the Indo-Pacific, SEB is more prevalent than any other coral disease (Page and Willis 2008) and is more common in polluted and warmer waters (Antonius and Lipscomb 2001;Willis etal. 2004;Winkler et al 2004). In contrast, the prevalence of the Caribbean ciliates appears to be higher in oceanic versus coastal human-influenced reefs (Croquer et al 2006a).…”
Section: Introductionmentioning
confidence: 75%
“…For example, skeletal eroding band (SEB) syndrome is related to a species of ciliate in the genus Halofolliculina, which affects corals in the Indo-Pacific and the Red Sea (Willis et al 2004;Winkler et al 2004;Page and Willis 2008). SEB had not, however, been reported in the Caribbean (Antonius andLipscomb 2001) until recently, when Croquer et al (2006a, b) found a folliculinid ciliate interacting with over 25 scleractinian coral species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that corals infected with BBD are more vulnerable to invasion by other pathogens at sites of tissue necrosis along the disease front. Conversely, it is also possible that initial BBD infections may be dependant on a previous injury (Antonius 1981a(Antonius ,b, 1985a, infection with another disease (Antonius 1977, 1981b, Winkler et al 2004 or compromised colony health. It is not possible to distinguish whether the co-occurrence of BBD and bleaching suggests that bleaching plays a role in the initiation or progress of BBD infection or vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, most coral diseases show a narrow distribution and occur within specific geographic regions only. For instance, the yellow band syndrome, white plague type II and dark spots are restricted to the Caribbean (Weil 2004), while other syndromes such as pink spots, porites ulcerative white spot disease, bacterial bleaching, brown band (BrB) and skeletal eroding band (SEB) have only been reported for the Indo-Pacific (Willis et al 2004) and the Red Sea (Winkler et al 2004). Even the few syndromes that are common to different bioregions appear to have a different etiology.…”
Section: Introductionmentioning
confidence: 99%